Formulasi Self-Nanoemulsifying Drug Delivery System (SNEDDS) dari Ekstrak Etanol Daun Pegagan (Centella asiatica) Sebagai Obat Antidiabetes Oral - Melati, Rynna; Setiyadi, Gunawan (Journal of Pharmaceutical and Sciences, 2025)
This research aims to develop a SNEDDS formulation based on the ethanolic extract of pegagan leaves (Centella asiatica). The goal is to improve the solubility and effectiveness of asiaticosida, an active compound that holds promise as a diabetes therapy. The extract is obtained through a soaking process with 96% ethanolic, resulting in a yield of 32.8%. The asiaticosida content in 200 mg of extract was analyzed using the HPLC method. To compile the SNEDDS, a combination of oils, surfactants, and cosurfactants that are most compatible with asiaticosida is selected. The selection results showed that soybean oil, Tween 20, and PEG 400 had the highest solubility levels: 375 mg/L, 115.73 mg/L, and 71.62 mg/L, respectively. This formulation used a 5:4:1 ratio of all three components, resulting in nanoemulsions with an average particle size of 127.6 nm, PDI 0.33, and a zeta potential of -45.86 mV that a best indicator of stability. Experimental results indicated that fast emulsification times and high levels of transmittance in various media (water, AGF, and AIF), approximately 47.33 s, respectively; 52.66 s; and 40.33 s, with a transmittance value above 85%. The nanoemulsion remained stable for 4 hours of observation. Further analysis showed that the asiaticosida dissolved in SNEDDS reached 12,34 ± 2,91 mg (4,11 mg/mL, n=3), slightly lower than the pure extract of dan 13,05 ± 2,62 mg (6,525%b/b, n=3). Overall, the SNEDDS of pegagan leaves show great potential as an innovation in the development of herbal medicines, especially for future clinical applications.